Household and climate factors influence Aedes aegypti presence in the arid city of Huaquillas, Ecuador - Martin, James L.; Lippi, Catherine A.; Stewart-Ibarra, Anna M.; Ayala, Efraín Beltrán; Mordecai, Erin A.; Sippy, Rachel; Heras, Froilán Heras; Blackburn, Jason K.; Ryan, Sadie J. (PLOS Neglected Tropical Diseases, 2021)
Author summary Mosquito transmitted infectious diseases are a growing concern around the world. The yellow fever mosquito (Aedes aegypti) has been responsible for recent major outbreaks of disease, including dengue fever and Zika. This mosquito prefers to bite humans and lay its eggs in artificial containers such as water tanks and planters. This makes Ae. aegypti well suited to become established in growing urban areas. Controlling these mosquitoes has been an important way to reduce the risk of disease transmission. Studies that are undertaken to understand local factors that contribute to the continued survival of the mosquito can be used to inform control practices. We conducted a study in the largest Ecuadorian city on the border of Peru where we collected adult mosquitoes from houses and surveyed household members about their behaviors, perceptions, and housing infrastructure associated with the mosquito vector. Mosquitoes were most numerous in weeks with high temperatures and a week after increased rainfall. We found that houses that had unreliable water service were more likely have mosquitoes present, while houses that used septic systems were less likely to have mosquitoes present.